POLA ASUH ORANGTUA DALAM MEMBENTUK KARAKTER ANAK - uswatun hasanah (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2016)
The main and first character education for children is a family environment. Education of family is very important and a fundamental pillar of the character development of a child. The family as the smallest social unit in an educational environment and most major responsibility to educate their children. The education given by parents supposed to provide the basis for the education of children about the process of socialization and life in society. Good parenting will bring positive impacts to the child’s development as well should. The success of character formation these children is influenced by the type of parenting parents in educating children. Parents play an important role in shaping the interaction system that intimate and lasting characterized by personal loyalty, love and loving relationship. Variety type of parenting parents consists of four kinds. First, authoritative; Second, authoritarian; and Third, permissive; as well Recently, indifferent. Each of parenting is having an impact for children’s development. The best parenting in the formation of character is the type of authoritative parenting. This, due to that the type of authoritative parenting is characterized by parents who tend to assume equal rights and responsibilities of children than he did because in practice this type of authoritative parenting, parents give freedom and guidance to children.